Formación didáctica del docente para la atención a la diversidad en cuarto año de Educación General Básica - Quishpi Guambo, Diana del Rosario (2020)
The present investigation starts from the problem observed in the fourth grade of Basic General Education, at the elementary public school “First of June”, where many teachers have difficulties in the attention to the diversity of the students they have in the classrooms of the classes, and in the application of didactics in the teaching-learning process, so these are not always fully effective. It is necessary that the teacher is trained from a didactic point of view, to carry out an effective learning teaching process, so the objective of the research was to determine the influence of teacher training in the attention to diversity in fourth year students. It was carried out with a mixed approach, where methods and techniques of the theoretical level, empirical level and mathematical level were used……….